Monetary policy shocks, expectations and information rigidities - Joscha Beckmann; Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2018)
This paper contributes to the literature by assessing expectation effects from monetary policy for the G7 economies. We consider a sample period running from 1995M1 to 2016M6 based on a panel VAR framework, which accounts for international spillovers and time-variation. Relying on a broad set of expectation data from Consensus Economics, we start by analyzing whether monetary policy has changed the degree of information rigidity after the emergence of the subprime crisis. We proceed by estimating potential effects of interest rate changes on expectations, disagreements and forecast errors. We find strong evidence for information rigidities and identify higher forecast errors by professionals after monetary policy shocks. Our results suggest that the international transmission of monetary policy shocks introduces noisy information and partly increases disagreement among forecasters.
Keywords: E31; E52; 330; Bayesian econometrics; expectations; information rigidity; monetary policy; panel VAR